The liver transplant risk score prognosticates the outcomes of liver transplant recipients at listing. Issue 6 (June 2021) - Kaltenmeier, Christof; Jorgensen, Dana; Dharmayan, Stalin; Ayloo, Subhashini; Rachakonda, Vikrant; Geller, David A.; Tohme, Samer; Molinari, Michele
Abstract: Background: We assessed if the risk of post-liver transplant mortality within 24 h could be stratified at the time of listing using the liver transplant risk score (LTRS). Secondary aims were to assess if the LTRS could stratify the risk of 30-day, 1-year mortality, and survival beyond the first year. Methods: MELD, BMI, age, diabetes, and the need for dialysis were the five variables used to calculate the LTRS during patients' evaluation for liver transplantation. Mortality rates at 24 h, 30 days, and 1-year were compared among groups of patients with different LTRS. Patients with ABO-incompatibility, redo, multivisceral, partial graft and malignancies except for hepatocellular carcinoma were excluded. Data of 48, 616 adult liver transplant recipients were extracted from the Scientific Registry of Transplant Recipients between 2002 and 2017. Results: 24-h mortality was 0.9%, 1.0%, 1.1%, 1.7%, 2.3%, 2.0% and 3.5% for patients with LTRS of 0, 1, 2, 3, 4, 5 and ≥ 6, respectively (P < 0.001). 30-day mortality was 3.5%, 4.2%, 4.9%, 6.2%, 7.6%, 7.2% and 10.1% respectively (P < 0.001). 1-year mortality was 8.6%, 10.8%, 12.9%, 13.9%, 18.5%, 20.3% and 28.6% respectively (P < 0.001). 10-year survival was 61%, 56%, 57%, 54%, 47%, and 31% for patients with 0, 1, 2, 3, 4, 5 and ≥ 6 points respectively (P < 0.001). Conclusion: Perioperative mortality and long-term survival of patients undergoing LT can be accurately estimated at the time of listing by the LTRS.